Rural Life In Shawkat Ali's Post-Liberation War Novels: The Conflict And Emergence Of Subaltern Consciousness (Journal of Namibian Studies : History Politics Culture, 2023)
The Bangladesh Liberation War once shook the entire world. The blood-soaked land of Bengal in 1971 presented the strength and resilience of its youth as a symbol of self-respect and dignity to the global community. However, the wounds inflicted on Bengal since 1947 remain unhealed. Even today, the cries of lost children, the agonizing wails of violated women, and the furious roars of rising fundamentalism echo in the alleys of Bengal. Bangladesh still suffers, unable to rise above the deluge of bloodshed. This is why the Liberation War occupies such a significant space in Bengali literature. From 1971 onwards, writers could not find solace in romantic poetry or imaginative tales. Their works became imbued with the grief of bereaved mothers, the stories of abused women, the chronicles of protests, and the echoes of marches. Shawkat Ali, a writer of that era, was no exception. His literary universe reflected the realities of the Liberation War, where truth replaced exaggeration, and reality superseded imagination. Even the smallest of events in his works are intricately tied to the Liberation War. A deeper exploration reveals that Shawkat Ali's entire life was shaped by the upheavals of the Liberation War. It is perhaps natural that his stories mirrored his surroundings.